(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article presents the problem of a fairy tale’s motive. The attention is drawn to the use of folkloric basis in the author’s text, its “modernity”, dependent on the work’s conception, outlook preferences and social cultural context. With the help of the examples of motives of dream and mirror in the Ukrainian literary tales of the second half of ХХ – beginning of ХХІ centuries semantic similarity is shown, connotative opportunities are discussed as well as productivity, connected with representation of the author’s outlook. In a fairy literary tale motives become an actualizer of its deep structure, they strengthen symbolic context, provide with several dimensions of the text.